Cēramāṉ Perumāṇāyaṉār aruḷicceyta Tiruvārūr mummaṇikkōvai - Cēramāṉ Perumāḷ Nāyaṉār, 9th cent (SAMP early 20th-century Indian books project ;, 1950)
Hymns in praise of the Hindu deity at Tiruvālūr, India.